2013
DOI: 10.1038/sc.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urodynamic findings in patients with upper and lower cervical spinal cord injury

Abstract: Study design: Retrospective study.Objectives: To analyze the neurogenic bladder characteristics and treatment approaches in patients with upper and lower cervical spinal cord injury (SCI) in order to make proper and reasonable decisions to the relevant patients. Setting: Rehabilitation center in Ankara, Turkey. Method: Ninety patients with cervical SCI were included. The urodynamic analyses of the patients were conducted retrospectively by using the urodynamic laboratory records. The patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
0
18
2
Order By: Relevance
“…However, UDI may elicit AD. Episodic blood pressure measurement has often been used during UDI to record AD [13,[17][18][19], but although continuous cardiovascular monitoring seems more accurate, since it may reveal even short episodes of AD, only one retrospective study [9] is available. Moreover, repeatability of cardiovascular changes during same session repeat UDI is unknown, and there is a complete lack of women-specific AD data.…”
Section: Introductionmentioning
confidence: 99%
“…However, UDI may elicit AD. Episodic blood pressure measurement has often been used during UDI to record AD [13,[17][18][19], but although continuous cardiovascular monitoring seems more accurate, since it may reveal even short episodes of AD, only one retrospective study [9] is available. Moreover, repeatability of cardiovascular changes during same session repeat UDI is unknown, and there is a complete lack of women-specific AD data.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, no significant difference was found regarding the frequencies of AD between C1-C5 and C6-C8 groups. 26 Giannantoni et al 15 found no correlation of AD to gender, age, disease duration or completeness of SCI. Huang et al 24 similarly showed no correlation of BP changes in relation to completeness of injury.…”
Section: Urodynamics and Cystometrymentioning
confidence: 99%
“…The incidence of AD during urodynamics varied [15][16][17]21,[23][24][25][26] ranging from 36.7% to 77.8%. This variation was influenced primarily by the neurological level and severity of the SCI.…”
Section: Incidence Of Ad During Iatrogenic Urological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, prescribed anticholinergic can affect the severe storage and emptying dysfunction of the bladder and improve bladder capacity. [3] Another, effective drug is baclofen, which has a positive effect on the bladder emptying function by relaxing the external sphincter. [4] This drug is commonly used in stroke patients.…”
mentioning
confidence: 99%